Clinical Trial Transparency: The FDA Should and Can Do More. Issue 4 (2017) - Kapczynski, Amy; Kim, Jeanie
Abstract : The Blueprint for Transparency at the FDA recommends that the FDA proactively release more clinical trial data. We show that the FDA possesses the legal authority to act on this recommendation, and describe several reasons that the agency should do so. In particular, the primary existing route for researchers to obtain access to this data, the Freedom of Information Act (FOIA), has important limits, as our own recent experience shows.